2013
DOI: 10.1140/epjc/s10052-013-2374-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the energy resolution and the tracking capabilities of a hybrid pixel detector with CdTe-sensor layer for a possible use in a neutrinoless double beta decay experiment

Abstract: Many different experiments are being developed to explore the existence of the neutrinoless double beta decay (0νββ) since it would imply fundamental consequences for particle physics. In this work we present results on the evaluation of Timepix detectors with cadmium-telluride sensor material to search for 0νββ in 116 Cd. This work was carried out with the COBRA collaboration and the Medipix collaboration. Due to the relatively small pixel dimension of 110 × 110 × 1000 µm 3 the energy deposited by particles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It has already been demonstrated that 1 mm thick CdTe layers can be assembled with the Timepix ASIC [19,20]. Other hybrid pixel detectors like the HEXITEC detector already have been successfully contacted to even 3 mm thick CdZnTe sensors with 80 × 80 pixels at 250 m pixel pitch [21].…”
Section: The Timepix Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that 1 mm thick CdTe layers can be assembled with the Timepix ASIC [19,20]. Other hybrid pixel detectors like the HEXITEC detector already have been successfully contacted to even 3 mm thick CdZnTe sensors with 80 × 80 pixels at 250 m pixel pitch [21].…”
Section: The Timepix Detectormentioning
confidence: 99%
“…Electron-positron tracks were generated by pair production. The experiment and the results were presented by Filipenko et al [20] in more detail. A 1 mm thick CdTe sensor layer with ohmic contacts (Pt) biased continuously at −500 V was exposed from the side to 2.614 MeV photons from the decay of 208 Tl.…”
Section: Energy Resolution Of Tracksmentioning
confidence: 99%
“…As a first step, we plan the global calibration of the Timepix chip. Improvements of the energy resolution of a factor between two and four are reported by [26] with a pixel by pixel calibration and this approach will be considered as a second step. Test of a 1 mm thick, 110 µm pixel side Timepix chip is also expected.…”
Section: Discussionmentioning
confidence: 99%
“…The Ikrum current both controls falling times of pulses generated by charge preamplifiers and compensates leakage currents (within the limit of Ikrum/2). All parameters were finally set to their default value, except Ikrum which was set to the DAC code value 2 corresponding to a falling time in the order of 1 µs [26]. It is important to notice that the pile-up is limited with such a value.…”
Section: Settings Of the Timepix Chip And Analysis Toolsmentioning
confidence: 99%
“…Ma et al reported multilayers of CdTe quantum dots as formaldehyde gases sensors. [10] Filipenko et al and Murphy et al also reported the use of single crystal and thin films CdTe as particle detectors for -particles, single electrons, and thermal neutrons [11,12]. An additional advantage of thin film CdTe is that it can be deposited using a wide variety of methods including sputtering, close-spaced sublimation, pulsed laser deposition, physical vapor deposition, among others [2,13,14].…”
Section: Introductionmentioning
confidence: 99%